The Utilization Of Cocopeat As Environmentally Friendly Composite - Soeparno Djiwo; E.Y. Setyawan; D.H Praswanto; T.N. Prihatmi; D. Hermawan (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2020)
The purpose of this study was to find environmentally friendly-based composite materials by utilizing natural materials that have been underutilized. The environmentally friendly composite is biodegradable which means that if it is not used it can decompose and will not affect or damage the environment. Not all natural ingredients are environmentally friendly; this depends on the application of the material. Composites made from cocopeat utilization can be applied to broad technical requirements. The maximum composite tensile strength test results were 13,473 MPa obtained in composites with 60% matrix with 40% coconut powder, shape and size using ASTM D638-3 and average impact strength 0,00994 J/mm2 obtained from composite 60% matrix with coconut powder 40 % the shape and size using ASTM D790-3, the process of using hand lay up. Adding a polyester matrix to the composite can increase the mechanical strength of the composite. On the other hand, excessive coconut powder in the mass fraction composite will reduce its mechanical strength. The observation of SEM photos in coconut powder shows the pores that can be used further to tie more matrices and able to increase the mechanical strength of the coconut powder composite.